Size And Rate Effects on the Fracture of Sea Ice. - Dempsey, John P. (1996)
This report contains the details of the experimental study as well as the theory applied to study the rate and size effect on the fracture of sea ice. To study the fracture of ice, experiments were carried out on a semi-circular bend fracture geometry. The test program formed a lab scale study to complement the in-situ large-scale sea ice fracture tests. The ice used was shipped back in the form of cores from the arctic tests. Two directions of fracture, parallel to the c-axis (optical axis) and perpendicular to the c-axis are studied. To examine the rate effect, a Reversed Direct Stress (RDS) device was modified to suit rectangular shaped test specimens. The details of modifications are given. Ice samples were subjected to creep-recovery loading and allowed to recover. The resultant time dependent deformations were analyzed using nonlinear viscoelastic theory. Experimental results as well as the details of the nonlinear viscoelastic models are given.